Autologous Fat Grafting in the Upper Extremity: Defining New Indications. Issue 8 (19th August 2022) - Deptula, Peter; Block, Tennyson; Tanabe, Kylie; Kulber, David
Abstract : Background: Autologous fat grafting is a commonly used technique in plastic surgery that can also be applied broadly in hand surgery. We present a case series to demonstrate the diverse indications for fat grafting in hand surgery. Methods: We retrospectively reviewed cases of fat grafting in the upper extremity in 2020. Cases representing a unique application of fat grafting were identified. Patient data, including demographics, diagnoses, preoperative and postoperative assessments, complications, patient satisfaction, and surgical operative reports, were recorded. Results: Five patients representing distinct indications for autologous fat grafting in the upper extremity were identified. Indications included hand rejuvenation (20.0%), burn/scar management (20.0%), tenolysis (20.0%), revision nerve decompression (20.0%), and carpometacarpal joint arthritis (20.0%). Average patient age was 60.4 years (range, 42–71). Average volume of fat injected was 15.2 ml (range, 1–37 ml). No major complications were noted (0.0%). All patients expressed satisfaction with their overall result with good functional outcomes (100%). Conclusions: Autologous fat grafting can be applied broadly in hand surgery. Indications for fat grafting in hand surgery include hand rejuvenation, burn/scar management, tenolysis, revision nerve decompression, and thumb carpometacarpal arthritis. Hand surgeons can easily incorporate fat grafting into their daily practice. Current literature supports fat grafting as a viable technique in hand surgery with lower-level studies.